Peripapillary atrophy with large dehiscences in bruch membrane in pseudoxanthoma elasticum: $hRichard F. Spaide, MD, Jost B. Jonas, MD, PHD - Spaide, Richard F.; Jonas, Jost B. (Retina, 2015)
Purpose: To describe a new set of findings in eyes with pseudoxanthoma elasticum, specifically large defects in Bruch membrane. Methods: Retrospective review of the optical coherence tomography image obtained with the Heidelberg Spectralis of the posterior pole of patients with pseudoxanthoma elasticum. Large dehiscences in Bruch membrane were defined as any defect in Bruch membrane greater than 250 µm in diameter that was not contiguous with a visible angioid streak. Results: There were 28 eyes of 14 patients, with a mean age of 53.6 years; 10 were female. Large dehiscences in Bruch membrane were seen in nine eyes of six patients, and all were within peripapillary atrophy manifested by loss of the choroid and retinal pigment epithelium. The edges of Bruch membrane showed an abrupt termination in the optical coherence tomography images, and often with an upturned edge surrounding the region devoid of Bruch membrane. The mean refractive error of the patients was -2.1 diopters (D) in the right eye and -2.5 D in the left. Conclusion: Pseudoxanthoma elasticum shares peripapillary atrophy and large dehiscences of Bruch membrane with pathologic myopia. Although theories of pathologic myopia involve stresses from ocular expansion, those of pseudoxanthoma elasticum typically do not. The Bruch membrane defect in pseudoxanthoma elasticum may be related to fragility secondary to abnormal calcification and to the surrounding abiotrophy of surrounding affected tissues of the posterior pole of the eye.